2020
DOI: 10.1029/2020gl087037
|View full text |Cite
|
Sign up to set email alerts
|

Eddies Affect Subsurface Phytoplankton and Oxygen Distributions in the North Pacific Subtropical Gyre

Abstract: The North Pacific Subtropical Gyre (NPSG) is an oligotrophic environment where a number of mesoscale eddies occur. With continuous measurements from Biogeochemical‐Argo (BGC‐Argo) floats, we showed that mesoscale eddies can significantly affect the subsurface chlorophyll maximum (SCM) and subsurface biogenic particles. Different responses of the SCM to the cyclonic and anticyclonic eddies and those between the eddy core and edge region were revealed by combining the results from tracked eddies. The variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 61 publications
5
38
2
Order By: Relevance
“…We could not detect the effects of meso-scale eddies on the micro-size plankton abundance (and also assemblages), whereas other studies [27][28][29] have reported that the phytoplankton abundance vary with the eddies. Several studies focused on the variations in chlorophyll a concentration, but micro-size plankton abundance and assemblages vary with meso-scale eddies, as reported by Davis and McGillicuddy [48].…”
Section: Plos Onecontrasting
confidence: 99%
See 1 more Smart Citation
“…We could not detect the effects of meso-scale eddies on the micro-size plankton abundance (and also assemblages), whereas other studies [27][28][29] have reported that the phytoplankton abundance vary with the eddies. Several studies focused on the variations in chlorophyll a concentration, but micro-size plankton abundance and assemblages vary with meso-scale eddies, as reported by Davis and McGillicuddy [48].…”
Section: Plos Onecontrasting
confidence: 99%
“…As several previous studies have indicated that phytoplankton abundance and assemblages differ with the eddy structure (cyclonic or anticyclonic) in the open ocean [ 27 29 ], we used relative vorticity (Ro) as the index of the eddy structure. Ro is calculated from the following equations where ζ is absolute vorticity, and f is the Coriolis parameter.…”
Section: Methodsmentioning
confidence: 99%
“…However, nuances are increasingly reported in eddy mechanisms and associated phytoplankton responses, highlighting the complexity of the phenomena in play (e.g., variations in physical fields through the eddy lifetime, contribution of lateral exchanges, eddy‐wind interaction, submesoscale pumping, eddy‐eddy interaction: Guidi et al., 2012 ; Lévy et al., 2001 ; McGillicuddy et al., 2007 ; Siegel et al., 2013 ; Sweeney et al., 2003 ). Among those modulations, variations are observed between the core sector of the eddies and their edge, the latter being subject to significant vertical motions impacting submesocale filaments and implying interactions with the surroundings waters (Klein & Lapeyre, 2009 ; Siegel et al., 2008 ; Xiu & Chai, 2020 ). Moreover, the respective influences of C and AC on phytoplankton dynamics are still debated (Barone et al., 2019 ; Brannigan, 2016 ; Dufois et al., 2016 ; Xiu & Chai, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among those modulations, variations are observed between the core sector of the eddies and their edge, the latter being subject to significant vertical motions impacting submesocale filaments and implying interactions with the surroundings waters (Klein & Lapeyre, 2009 ; Siegel et al., 2008 ; Xiu & Chai, 2020 ). Moreover, the respective influences of C and AC on phytoplankton dynamics are still debated (Barone et al., 2019 ; Brannigan, 2016 ; Dufois et al., 2016 ; Xiu & Chai, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two reasons were considered for our results on the meso-scale eddies, namely 1) the difference in observation of oceanic basins, and 2) the limitations of our approach (observations and statistical models). First, previous studies had been conducted in the central and eastern NPSG [27][28][29], and the heterogeneity of plankton abundance and assemblages with the meso-scale eddies are observed rarely in the western NPSG. Second, our data sets were a mixture of observations of three cruises, of which the primary aims were investigation of the distribution of Japanese eel larvae.…”
Section: Plos Onementioning
confidence: 99%